DAMPAK DIGITALISASI TERHADAP PERAN FRONT OFFICE DALAM BISNIS PERBANKAN - Salmah Salmah; Andreas Murti (Universitas Pakuan, 2020)
This study aims to review and analyze the impact of banking digitalization to front office functions in the banking business in the city of Bogor. Data collection was carried out by gathering information from stakeholders and branch managers of the two state-owned banks in Bogor City through questionnaires and interviews with informants. The data processed in a descriptive statistics methods. The results of data collection from 2016-2018 at ABC Bank showed fairly consistent growth for transactions with m-banking and internet banking. While for XYZ Bank, transaction with m-banking increased significantly, while transactions through internet banking declined slightly, but in total both transactions increase significantly. This shows the preferences of XYZ bank customers who tend to use smartphones in banking transactions. The majority of respondents agreed that m-banking and internet banking with all the conveniences and features that are constantly being updated will be able to take over the role and duties of the front office in the future. Teller and customer service must adapt with technology and continue to develop their skill so they can compete and keep contributing in banking business.